A Study on Sheep Farming Management to Produce High Quality Sheep in Kuching, Sarawak - Angelina Emma, Pincheu; Farah Aina Affifah, Fallah Reza; Iman Qistina, Azhar; John Jelian, Maurice Medan; Pamela Eleanor, Abu; Hung Hui, Chung (UNIMAS Publisher, 2025)
Global population growth and economic development have an impact on agricultural sectors. If the human population continues to grow at its current rate, there will be a food shortage issue, which must be addressed, particularly in developing countries. The food supply maintenance is crucial to avoid poverty, which might have an impact on overall economic development. To prevent this hurdle from happening, achieving agricultural growth is crucial. One of the most in-demand agricultural products is livestock and it is the fastest growing industry in many countries. Livestock usually includes cattle, goats, chickens and sheep.